A Case of Dwarfism from the Byzantine City Rehovot‐in‐the‐Negev, Israel. (14th September 2011) - Slon, V.; Nagar, Y.; Kuperman, T.; Hershkovitz, I.
ABSTRACT Skeletons of dwarfs have been found in many archaeological sites from around the world. Nevertheless, their descriptions (morphologically and metrically) are very limited. We describe herein the skeleton of a male dwarf, approximately 35–50 years old, found in the Byzantine cemetery (5th–8th century CE) of Rehovot‐in‐the‐Negev, southern Israel. Living stature was estimated at 120–125 cm. Detailed morphological skeletal descriptions and morphometric analysis, together with computed tomography (CT) observations, suggest a diagnosis of achondroplasia. The long bones anomalies, in tandem with other features such as hydrocephalus and spinal stenosis, are discussed in regard to their effect on the dwarf's daily life. The putative place of dwarfs in early Christian communities, compared with dwarfs from other times and places, will be addressed. Copyright © 2011 John Wiley & Sons, Ltd.